159 INTERACTIONS OF FGFS AND TRANSFORMING GROWTH FACTOR β1 IN DEVELOPING LUNG. (1st January 2006) - Xing, Y. M.; Li, C. G.; Minoo, P.
Abstract : Purpose of Study: Branching morphogenesis of the pulmonary epithelium is a highly regulated process that involves cell proliferation, migration, and differentiation. Signaling and transcription factors are known to play key roles in this process. For example, FGFs and in particular FGF10 stimulate branching morphogenesis, whereas TGF-beta inhibits it. Two important questions addressed by the following study were (1) what is the interaction between FGFs and TGF-beta and (2) whether the effect of TGF-beta is mediated through Smad3, one of its downstream transcriptional effectors. Methods: Mesenchyme-free lung endodermal tissue from lungs of embyronic day 12.5 wild-type and Smad3(-/-) mouse embryos were isolated and used in Matrigel explant cultures in the presence or absence of various growth factors. At designated time points, explants were photographed and analyzed for growth and/or branching activity. Summary of Results: FGF10 alone induced branching activity in wild-type endodermal explants. In contrast to FGF10, FGF7-treated explants underwent a process of generalized growth that resulted in formation of cyst-like structures instead of budding. Addition of TGF-beta1, TGF-beta2, or TGF-beta3 strongly inhibited FGF10-induced beanching activity. However, the inhibitiory effect of TGF-beta was significantly reduced in explants derived from Smad3(-/-). Conclusions: We provide evidences that TGF-beta1 inhibits FGF10-induced branching activity in early lung endodermal explants. The inhibitory impact of TGF-beta is mediated to a large extent by the activation of Smad3. Supported by the Hastings Foundation, HL56590 and HL073471.